(untitled) (Academia Journal of Medicine, 2024)
The COVID-19 pandemic has posed a major global health challenge, especially for individuals with underlying health issues. This study aimed to assess the clin ical outcomes of vitamin D supplementation in patients with moderate to severe COVID-19 in a tertiary care hospital through a randomized clinical trial. Sixty two SARS-CoV-2 positive patients were enrolled and divided into intervention (vitamin D supplementation) and control groups.